Responses of Antioxidant Defense and Immune Gene Expression in Early Life Stages of Large Yellow Croaker (Pseudosciaena crocea) Under Methyl Mercury Exposure - Wu, Fangzhu; Huang, Wei; Liu, Qiang; Xu, Xiaoqun; Zeng, Jiangning; Cao, Liang; Hu, Ji; Xu, Xudan; Gao, Yuexin; Jia, Shenghua (Frontiers in Physiology, 2018)
Early life stages (ELS) of marine organisms are the most sensitive stages to environment stressors including pollutants. In order to understand the toxicological effects induced by MeHg exposure on juveniles of large yellow croaker (Pseudosciaena crocea), a toxicity test was performed wherein fish were exposed to sub-lethal concentrations of MeHg under laboratory conditions (18±1 °C; 26±1 in salinity). After 30 days of 0-4.0 μg L-1 MeHg exposure, SOD activity was significantly decreased in the 0.25, 1.0 and 4.0 μg L-1 treatments; while CAT activity was significantly increased in the 4.0 μg L-1 treatments; GSH level, GPx activity were significantly elevated in the 4.0 μg L-1 treatments, respectively. Meanwhile, MDA content was also significantly increased in the 1.0 and 4.0 μg L-1 treatments with respect to the control. AChE activity was significantly decreased by 18.3%, 25.2% and 21.7% in the 0.25, 1.0 and 4.0 μg L-1 treatments, respectively. The expression of TCTP, GST3, Hsp70, Hsp27 mRNA were all up-regulated in juveniles with a dose-dependent manner exposed to MeHg. These results suggest that large yellow croaker juveniles have the potential to regulate the levels of antioxidant enzymes and initiate immune response in order to protect fish to some extent from oxidative stress induced by MeHg.